Passive radiative thermal management using phase-change metasurfaces - Singh, Leena; Qiu, Erbin; Cardin, Andrew E; Chen, Aiping; Luk, Ting S; Schuller, Jon A; Dalvit, Diego A R; Schuller, Ivan K; Kort-Kamp, Wilton J M; Azad, Abul K (JPhys photonics, 2025)
Realizing innovative composite materials with passive thermal management capabilities and minimal ecological footprints is a challenging but much sought-after goal that would have a transformative effect on renewable energy sciences. We demonstrate an environmentally friendly metasurface utilizing vanadium dioxide (VO 2 ) that offers responsiveness to ambient temperature and potentially long-term stability. The metasurface enables passive thermal management by self-adjusting its absorptivity and emissivity response over a broad bandwidth ranging from visible to mid-infrared (IR) wavelengths. Above the VO 2 phase transition the metasurface exhibits increased mid-IR emissivity and reduced visible/near-IR absorptivity, creating an efficient radiative emission channel in the first atmospheric transparency window with reduced absorption of solar radiation. In contrast, below VO 2 ’s transition temperature, the metasurface increasingly absorbs sun light while minimizing mid-IR radiative heat losses. Moreover, a functional silicon layer eliminates the need for an additional capping layer commonly employed to protect VO 2 from environmental degradation. The additional protective layer often impedes the use and performance of VO 2 based devices in terrestrial as well as spacecraft applications. Therefore, the proposed durable and eco-friendly metasurface will be an excellent candidate for essential passive thermal regulation systems across residential and terrestrial applications.